THE MECHANICAL BEHAVIOUR OF SIC FIBRES IN A TI MATRIX DURING FABRICATION BY VACUUM PLASMA SPRAYING AND VACUUM HOT PRESSING - Zhao, Y; Grant, P; Guo, Z; Cantor, B (Minerals, Metals and Materials Soc (TMS), 1995)
The mechanical behaviour of uncoated and TiBx/C coated continuous DRA SIGMA SiC fibres during manufacture of Ti MMC monotapes by vacuum plasma spraying (VPS) and subsequent consolidation by vacuum hot pressing (VHP) has been compared. The mean tensile strengths of as received uncoated and TiBx/C coated SIGMA SiC fibres are 3.2 and 3.5 GPa respectively. The uncoated fibre has a lower tensile strength than the coated fibre because it is more susceptible to surface damage during handling. VPS and VHP have been successfully combined to produce Ti/SiCf composites with very uniform fibre distribution and reduced interfacial reaction. Uncoated SiC fibres are susceptible to premature fracture during VPS and VHP processing, resulting from thermal mismatch and direct applied compressive stresses. Under the same VPS and VHP processing conditions, TiBx/C coated SiC fibre do not fracture, partly because of a higher initial tensile strength, and partly because the coating acts as a compliant layer relatively weakly bonded to the fibre.